Presbycusis: do we have a third ear? - Reis,Luis Roque (2016)
Abstract Introduction: Age-related hearing changes are the most frequent cause of sensorineural hearing loss in adults. In the literature no studies exist concerning the importance of speechreading in individuals with presbycusis. Equally, no such studies have been carried out with speakers of the Portuguese (Portugal) language. Objectives: To evaluate whether the intelligibility of words in presbycusis is improved by speechreading, in such a way that looking at the interlocutor's face while he is talking functions like a “third ear”, and to determine the statistical relevance of the intelligibility improvement by speechreading. Methods: Eleven individuals (22 ears) with bilateral and symmetrical sensorineural hearing loss compatible with presbycusis were evaluated. The subjects were aged between 57 and 82 years, with an average of 70 ± 11.51 years and median of 69.5 years. A complete medical and audiological profile of each patient was created and all patients were submitted to a vocal audiogram, without and with observation of the audiologist's face. A descriptive and analytical statistical analysis was performed (Shapiro-Wilk and t pairs tests) adopting the significance level of 0.05 (5%). Results: We noticed better performance in intelligibility with speechreading. The p-value was zero (p < 0.05), so we rejected the null hypothesis, showing that there was statistically significant difference with speechreading; the same conclusion was obtained by analysis of the confidence intervals. Conclusions: Individuals with presbycusis in this study, performed better on spoken word intelligibility when the hearing of those words was associated with speechreading. This phenomenon helps in such a way that observation of the interlocutor's face works like a "third ear".